1974
DOI: 10.1002/j.1537-2197.1974.tb12307.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of the Nodal and Vascular Anatomy in the Neotropical Cyatheaceae. Iii. Nodal and Petiole Patterns; Summary and Conclusions

Abstract: Comparative studies of the nodal and vascular anatomy in the Cyatheaceae are discussed as they relate to the taxonomy and phylogeny of the family. There is in the Cyatheaceae (excluding Metaxya and Lophosoria) a basic nodal pattern consisting of four major phases of leaf trace separations. Abaxial traces arise from the leaf gap margins, and the last abaxial traces from each side of the gap are larger and undergo numerous divisions. Distally adaxial traces separate from the gap margins, and the last adaxial tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
1

Year Published

1976
1976
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 10 publications
(8 reference statements)
1
36
1
Order By: Relevance
“…Both genera are characterized by marginate petiole scales that lack apical setae, and the cellular differentiation of the scales is similar in both taxa. The stelar pattern in the mature stem is basically similar in both Trichipteris and Cyathea (Lucansky, 1974). In the species studied the stelar pattern is a dictyostele with overlapping leaf gaps and consists of individual meristeles, each surrounded by sclerenchymatous tissue ( Fig.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Both genera are characterized by marginate petiole scales that lack apical setae, and the cellular differentiation of the scales is similar in both taxa. The stelar pattern in the mature stem is basically similar in both Trichipteris and Cyathea (Lucansky, 1974). In the species studied the stelar pattern is a dictyostele with overlapping leaf gaps and consists of individual meristeles, each surrounded by sclerenchymatous tissue ( Fig.…”
mentioning
confidence: 78%
“…RESULTS AND DISCUSSION-Based upon habit, stem and petiole indument, stelar pattern, and the nodal anatomy of mature plants, Trichipteris and Cyathea show affinities and an evolutionary relationship (Tryon, 1970;Lucansky, 1974;Lucansky and White, 1974). Yet, comparative ana- 253 ALTHOUGH MORPHOLOGICAL similarities exist, Trichipteris (90 species) and Cyathea (11 0 species) represent separate evolutionary lines.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ogura (1972) discussed petiolar phloem in the ferns and described a range of bundle types from collateral to concentric. Although Ogura (1972) and other authors (Bertrand and Cornaille, 1902;Lin andDevol, 1977, 1978;Lucansky and White, 1974) have found that petiolar anatomy can sometimes be used as a taxonomic character, there are too many inconsistencies in the distribution of different types to utilize this character alone in constructing phylogenies. The petiolar trace in several Carboniferous ferns (e.g., Etapteris, Ankyropterist is radially symmetrical in transverse section, and thus cannot be compared to most extant filicaleans, which exhibit bilaterally symmetrical petiole traces.…”
Section: Ankyropteris-general Anatomymentioning
confidence: 99%